Facile preparation of poly(vinyl alcohol)/graphene oxide nanocomposites and their foaming behavior in supercritical carbon dioxide. (April 2018) - Liu, Pengju; Chen, Wenhua; Bai, Shibing; Wang, Qi; Duan, Wenfeng
Graphical abstract: Abstract: In this study, we presented a novel polymer nanocomposite foam based on poly(vinyl alcohol) (PVA) and graphene oxide (GO) prepared via the supercritical fluid foaming technology. By using water as the benign solvent, GO sheets were fully exfoliated and homogeneously dispersed into PVA matrix with the assistance of mild sonication, and then the PVA/GO nanocomposite was obtained after thermal processing. The results indicated that the well-dispersed PVA/GO nanocomposite showed significantly improved mechanical strength, compared with neat PVA. In subsequent foaming procedure, GO sheets served as the reinforcing element for cell walls and played an effective role in stabilizing the cellular structure during cell growth. Benefiting from the heterogeneous nucleation of GO sheets, the nanocomposite foams exhibited smaller cell size and larger cell density, thus a remarkable enhancement in compressive strength was obtained for PVA/GO nanocomposite foams.